2016
DOI: 10.1039/c6cc06060a
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric aerobic oxidative NHC-catalysed synthesis of dihydropyranones utilising a system of electron transfer mediators

Abstract: In the context of green chemistry, the replacement of high molecular weight stoichiometric oxidants with O2 is most desirable but difficult. Here, we report the asymmetric aerobic oxidative synthesis of dihydropyranones. The oxidation is aided by a system of electron transfer mediators and is selective toward the homoenolate. The dihydropyranones can be isolated in high to excellent yields, with high ee (up to 95%).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 56 publications
0
31
0
Order By: Relevance
“…Treatment with equimolar amounts of NHC precatalyst 4 and 1,8-diazabicyclo [5.4.0]undec-7-ene (DBU) in methanol yielded the ringopened diketoester 3 in 95 % yield, as previously reported. 39 However, usage of slightly higher loadings of DBU (15 mol%) in absence of 4 yielded compound 2 in 89% isolated yield. A stochiometric amount of methyl acetate was also detected in the crude reaction mixture by 1 H NMR, suggesting that 2 is formed via a retro-Claisen fragmentation of the 1,3-diketone of compound 3.…”
Section: Results and Discussion Reaction Optimization And Scopementioning
confidence: 99%
See 3 more Smart Citations
“…Treatment with equimolar amounts of NHC precatalyst 4 and 1,8-diazabicyclo [5.4.0]undec-7-ene (DBU) in methanol yielded the ringopened diketoester 3 in 95 % yield, as previously reported. 39 However, usage of slightly higher loadings of DBU (15 mol%) in absence of 4 yielded compound 2 in 89% isolated yield. A stochiometric amount of methyl acetate was also detected in the crude reaction mixture by 1 H NMR, suggesting that 2 is formed via a retro-Claisen fragmentation of the 1,3-diketone of compound 3.…”
Section: Results and Discussion Reaction Optimization And Scopementioning
confidence: 99%
“…For instance, both Smith et al and our group have observed facile ring-opening with methanol when using Brønsted bases (Scheme 2 A). 39,46 Huang et al have shown that it is possible to extend this type of reaction by treating the acyclic ester with either hydrazine or hydroxylamine, yielding pyrazoles or isoxazoles respectively. 41 A diastereoselective epoxidation of the enol double bond using m-CPBA with only slight erosion of enantiopurity was developed by Chi and coworkers (Scheme 2 B).…”
Section: Scheme 2 Reactivity Of Dihydropyranonesmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the authors considered that the possible oxygenative path of the investigated mechanism occurs in the minority of cases. Sundén and co-workers reported the aerobic NHC-catalyzed synthesis of dihydropyranones via multistep electron transfer in 2016 ( Figure 11) [53]. The assumption of this work is the oxidation of ETM first, by oxygen from air.…”
Section: Oxidative Nhc Catalysismentioning
confidence: 89%